BIOGENIC SYNTHESIS OF SILVER NANOPARTICLES FROM THE LEAF EXTRACT OF SYZYGIUM CUMINI(L.)AND ITS ANTIBACTERI - RAM PRASAD; V. SATYANARAYANA SWAMY; KUMAR SURANJIT PRASAD; AJIT VARMA (International Journal of Pharma and Bio Sciences, 2012)
The antimicrobial activity of silver nanoparticles with the clinically important microbes is a major area of research in the field of nanobiotechnology. Syzgium cumini (L.) is used as medicinal plant for anti-diabetic property. The leaves and bark are used for controlling blood pressure and gingivitis. In this present study, we have synthesized silver nanoparticles using Syzygium cumini leaf extract. The leaf extract of S. cumini is used as capping and reducing agent in the synthesis of silver nanoparticles. The formation of nanoparticles was confirmed by UV-Vis spectrophotometer, Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM). Further antimicrobial activity of silver nanoparticles was studied against Escherichia coli MTCC 1302, Staphylococcus aureus MTCC 740, Pseudomonas aeruginosa MTCC 2295, and Bacillus licheniformis MTCC 9555. Surface Plasmon resonance of silver nanoparticles was recorded at 400 nm by UV-Vis spectrophotometer. The synthesized nanoparticles are spherical and having size ranging from 100- 160 nm.